The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/asj.12357
|View full text |Cite
|
Sign up to set email alerts
|

The g.841G>C SNP of FASN gene is associated with fatty acid composition in beef cattle

Abstract: The objective of the current study is to evaluate the association between fatty acid composition and fatty acid synthase gene polymorphisms as responsible mutations. For this purpose, we selected seven previously reported single nucleotide polymorphisms (SNPs) in FASN gene, including one within promoter region (g.841G>C) and six non-synonymous SNPs (g.8805C>T, g.13126C>T, g.15532A>C, g.16024A>G, g.16039C>T, g.17924A>G), and genotyped them in Japanese Black cattle. Genotyping results revealed that g.8805 C>T an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…(), or association test in many populations with different genetic background such as in Hayakawa et al . (). However, our study performed GWAS with many traits that were difficult to measure, and both methods could not be applicable.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(), or association test in many populations with different genetic background such as in Hayakawa et al . (). However, our study performed GWAS with many traits that were difficult to measure, and both methods could not be applicable.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, the g.841G > C mutation in FASN showed stronger association with fatty acid composition than those of g.16024A > G (Hayakawa et al . ). The g.16024A > G mutation was not related to carcass traits (Matsuhashi et al .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies based on candidate gene approaches had revealed polymorphisms within FASN that were related to fatty acid composition in multiple beef cattle populations [45–49] and milk fat content in dairy cattle [50, 51]. For instance, several studies were conducted to explore and evaluate the association between fatty acid composition and candidate SNPs using GWAS in Japanese beef cattle [8, 30, 52]. These studies provided multiple evidences that several SNPs near or within FASN may be regarded as responsible mutations for fatty acid composition and contribute largely to meat quality in the Japanese Black cattle population.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Hayakawa et al . () revealed that the g.841G>C SNP of FASN gene had significant associations with FA composition traits (C14:0, C14:1, C16:1, C18:1). Therefore, the A haplotype of GH locus would be responsible for the presence of C14:0 as well as the g.841G>C SNP of FASN gene in JBK, at least in S.…”
Section: Discussionmentioning
confidence: 99%